Q. 345.0( 1 Vote )
Answer each of th
Given sin-1 (1/3) + cos-1 x = π/2
⇒ sin-1 (1/3) = π/2 – cos-1 x
We know that sin-1 x + cos-1 x = π/2
⇒ sin-1 (1/3) = sin-1 x
∴ x = 1/3
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation